Microbial Communities and Chemosynthesis in Yellowstone Lake Sublacustrine Hydrothermal Vent Waters - Yang, Tingting; Lyons, Shawn; Aguilar, Carmen; Cuhel, Russell; Teske, Andreas (Frontiers in Microbiology, 2011)
Five sublacustrine thermal spring locations from 1 to 109 m water depth in Yellowstone Lake were surveyed by 16S ribosomal RNA gene sequencing in relation to their chemical composition and dark CO2 fixation rates. They harbor distinct chemosynthetic bacterial communities, depending on temperature (16–110°C) and electron donor supply (H2S <1 to >100 μM; NH3 <0.5 to >10 μM). Members of the Aquificales, most closely affiliated with the genus Sulfurihydrogenibium, are the most frequently recovered bacterial 16S rRNA gene phylotypes in the hottest samples; the detection of these thermophilic sulfur-oxidizing autotrophs coincided with maximal dark CO2 fixation rates reaching near 9 μM C h−1 at temperatures of 50–60°C. Vents at lower temperatures yielded mostly phylotypes related to the mesophilic gammaproteobacterial sulfur oxidizer Thiovirga. In contrast, cool vent water with low chemosynthetic activity yielded predominantly phylotypes related to freshwater Actinobacterial clusters with a cosmopolitan distribution.